Children's Premier - Pinker, Edieal (SAGE Knowledge. Cases., 2016)
When Stan Green received an appointment at Yale University in 2013, he moved his family to Greenwich Connecticut. The relocation meant a number of changes, including finding a new pediatrician for his two children. He chose Children's Premier, a group practice in Greenwich that was a short drive from his new home. Less than a month after enrolling, however Green got a letter from Children's Premier that left him wondering what was up with the group and whether he should consider taking his children elsewhere.